Perlukah ICT dalam Strategi Managemen Komunikasi Penyedia Kursus Bahasa - Enggal Sriwardingsih (Binus Business Review, 2012)
Perfect competition between the English language course requires the use of technology and communication (ICT) between service providers and consumer, that is recognized as a strategy to enhance corporate value in the eyes of its customers. But the needs of required for input to the base system's technology into its own problems in order to become a competitive advantage for companies in the face of business competition. Porter and SWOT analysis to assess the indicators that are needed to further diimplemenasikan in ICT in the future need.